INSULATION COMPOSITE PLASTER FOR ENERGY-SAVING CONSTRUCTION - I.G‘.Ahmedov; I.I.Umarov (Journal of new century innovations, 2023)
Abstract. The article deals with the use of finishing slabs from gypsum heat- insulating composite materials based on industrial waste in energy-efficient construction, the compositions and properties of these materials are considered.